Salmond, Necessity, and the State - Frame, Alex (Victoria University of Wellington Law Review, 2008)
This article explores the varying approaches of Sir John Salmond as government adviser, judicial office, and legal theorist, to the State and the circumstances under which it might act under "necessity" in disregard of law. An epilogue provides the writer's own attempt in formal advice to delineate the boundaries of the doctrine in modern jurisprudence.